The effect of self management in the hardiness at work / study analytic in hospital Alshaheed Gaze Alharery - الطائي, علي حسون; رحيمة, سلمى حتيتة (Journal of Economics and Administrative Sciences, 2011)
The research is Concerned the Relationship between Self Management which is a modern administrative term and its dimensions "Self Control, Trust, and Conscientiousness" with the Hardiness and its dimensions "Challenge, Commitment, and Control". And the impact of the first variable on the second in The Hospital of Alshaheed Gaze Alharery. The Questionnaire used and distributed on sample (60) Persons, contain from (40) Doctor, and (20) Employees from the total society (103).The statistical methods have been used for testing the hypothesis is the mean, standard deviation correlation coefficient.    The research ended some conclusions and recommendations which contribute in developing the research variables.